MARKETING STRATEGY ANALYSIS IN INCREASING SALES AT FAYZA BUSANA CILEUNGSI (SHARIAH ECONOMIC PERSPECTIVE) - Nur Fanny Oktavia; Ermi Herawati; Muhammad Salman Al Farisi (JURNAL PROFIT, 2025)
This study aims to analyze marketing strategies for increasing sales at Fayza Busana Cileungsi from the perspective of Islamic economics. The method used is a qualitative method with a case study approach. Data collection techniques by conducting interviews, observation, and documentation. The data analysis technique used SWOT analysis. The results showed that the marketing strategy used was Segmentation, Targeting, and Positioning, as well as the 7P marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) with sharia marketing characteristics Rabbaniyah, Waqi'iyah, Akhlaqiyyah, and Al-Insaniyyah. The Internal Factor Analysis Summary table shows positive results with a score value of 0.12 and the External Factor Analysis Summary table shows negative results with a score value of -0.19. The results of data processing using a Cartesian diagram show the position of Fayza Busana in quadrant II with alternative strategies that can be carried out using the ST (Strengths-Weaknesses) strategy, which is to utilize internal strengths to avoid or reduce external threats.